A critical re-evaluation of multilocus sequence typing (MLST) efforts in Wolbachia. Issue 1 (23rd November 2017) - Bleidorn, Christoph; Gerth, Michael
Abstract: Wolbachia (Alphaproteobacteria, Rickettsiales) is the most common, and arguably one of the most important inherited symbionts. Molecular differentiation of Wolbachia strains is routinely performed with a set of five multilocus sequence typing (MLST) markers. However, since its inception in 2006, the performance of MLST in Wolbachia strain typing has not been assessed objectively. Here, we evaluate the properties of Wolbachia MLST markers and compare it to 252 other single copy loci present in the genome of most Wolbachia strains. Specifically, we investigated how well MLST performs at strain differentiation, at reflecting genetic diversity of strains, and as phylogenetic marker. We find that MLST loci are outperformed by other loci at all tasks they are currently employed for, and thus that they do not reflect the properties of a Wolbachia strain very well. We argue that whole genome typing approaches should be used for Wolbachia typing in the future. Alternatively, if few loci approaches are necessary, we provide a characterisation of 252 single copy loci for a number a criteria, which may assist in designing specific typing systems or phylogenetic studies. Abstract : Wolbachia MLST genes are too conserved to allow strain differentiation, do not reflect genome wide divergence rates, and are poor phylogenetic markers.